Binky to the rescue - Spires, Ashley, 1978- (Spires, Ashley, 1978- Binky adventure., 2010)
A loveable and delusional house cat named Binky, who, while in hot pursuit of an alien wanderer (a bug), falls out of the space station porthole (the bathroom window), and finds himself in outer space (outside the house).